2016
DOI: 10.1364/boe.7.003543
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body multispetral photoacoustic imaging of adult zebrafish

Abstract: The zebrafish, an ideal vertebrate for studying developmental biology and genetics, is increasingly being used to understand human diseases, due to its high similarity to the human genome and its optical transparency during embryonic stages. Once the zebrafish has fully developed, especially wild-type breeds, conventional optical imaging techniques have difficulty in imaging the internal organs and structures with sufficient resolution and penetration depth. Even with established mutant lines that remain trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Photoacoustic imaging is a non-invasive imaging modality offering an increased in vivo imaging depth and spatial resolution compared to other traditional optical imaging methods [ 37 40 ]. We found that AuNR-PEG with high NIR absorbance could be used as a great contrasting agent in photoacoustic imaging (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Photoacoustic imaging is a non-invasive imaging modality offering an increased in vivo imaging depth and spatial resolution compared to other traditional optical imaging methods [ 37 40 ]. We found that AuNR-PEG with high NIR absorbance could be used as a great contrasting agent in photoacoustic imaging (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because of this pressing need, a gamut of modalities have been tried and used to image adult zebrafish: optical projection tomography (OPT), 1,2 photoacoustic tomography (PAT), 3,4 optical multispectral 3D tomography, 5 time‐gated optical projection tomography (TGOPT), 6 optical coherence tomography (OCT), 7 contrast‐enhanced X‐ray micro‐computed tomography, 8 synchrotron X‐ray micro‐computed tomography (SR‐CT), 9 ultrasound, 10 and NMR microscopy (MRM) ex vivo 11 and in vivo. 1216…”
Section: Introductionmentioning
confidence: 99%
“…The generated PA signals are collected by a 10 MHz cylindrically focused US transducer (V311, Olympus Inc.) and amplified at ~66 dB using a customized amplifier. The lateral and axial resolutions of the system were estimated to be 80 and 600 μm using phantom experiments, respectively . For US imaging, a pulse/receiver (5073PR, Olympus Inc.), synchronized with the output trigger of the OPO laser, drives a 7.5 MHz spherical‐focused transducer (V320, Olympus Inc.) to generate acoustic waves, records and amplifies the reflected acoustic signals.…”
Section: Methodsmentioning
confidence: 99%